2015
DOI: 10.3171/2015.1.spine14515
|View full text |Cite
|
Sign up to set email alerts
|

Myelopathy-mimicking symptoms of epidural venous engorgement and syringomyelia due to inferior vena cava stenosis at the thoracolumbar junction in a patient with Budd-Chiari syndrome

Abstract: Epidural venous engorgement can result from various lesions, such as arteriovenous malformation, thrombosis or occlusion of the inferior vena cava (IVC), or an abdominal masslike lesion. Most patients with these problems complain of low-back pain, radicular pain, or neurogenic claudication, which are symptoms suggestive of disc herniation or spinal stenosis. However, these patients rarely exhibit neurological deficits or cauda equina syndrome. The authors encountered a case of a 60-year-old man present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…The final studies included were case reports or series. Eighteen reports referred to abdominal conditions that mimic spinal diseases ( Table 1 ), 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 among them a patient with cyclic lumbar back pain who received a lumbar spinal fusion who, after persisting symptoms led to further diagnostic procedures, was ultimately diagnosed with endometriosis. 15 Spinal symptoms included paraplegia and urinary incontinence as results of acute aortic pathologies.…”
Section: Literature Review and Discussionmentioning
confidence: 99%
“…The final studies included were case reports or series. Eighteen reports referred to abdominal conditions that mimic spinal diseases ( Table 1 ), 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 among them a patient with cyclic lumbar back pain who received a lumbar spinal fusion who, after persisting symptoms led to further diagnostic procedures, was ultimately diagnosed with endometriosis. 15 Spinal symptoms included paraplegia and urinary incontinence as results of acute aortic pathologies.…”
Section: Literature Review and Discussionmentioning
confidence: 99%
“…There are only 20 previously reported cases of myelopathy associated with EVPE secondary to IVC thrombosis, only five of which exhibited symptoms of CES [ Table 1 ]. [ 1 2 4 5 7 8 9 10 12 13 ] Anticoagulation, pharmacomechanical thrombectomy, and IVC stenting were the treatment of choice in many of these cases. Here, following a decompressive laminectomy to rule out an epidural abscess and resect the anteriorly massive dilated L5-S1 venous plexus, the patient's symptoms resolved.…”
Section: Discussionmentioning
confidence: 99%
“…This rarity of IVC occlusion as an etiology for radiculopathic pain is demonstrated by Paksoy et al, who found in a cohort of 9,640 patients with lumbar back pain or radiculopathic symptoms that only 10 patients had an underlying IVC thrombosis [ 19 ]. Engorgement of Batson’s plexus culminating in radiculopathic pain has been reported for a few rare disease processes: IVC obstruction secondary to Budd-Chiari syndrome, arteriovenous malformation, thrombosis, or a compressing abdominal mass [ 20 - 22 ]. Although diagnostically challenging because it closely mimics much more common pathologies such as disc herniation or spinal stenosis, cord compression secondary to engorgement of the epidural venous plexus must be considered on the differential for all patients with an IVC filter who present with lower extremity pain or weakness [ 19 - 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Engorgement of Batson’s plexus culminating in radiculopathic pain has been reported for a few rare disease processes: IVC obstruction secondary to Budd-Chiari syndrome, arteriovenous malformation, thrombosis, or a compressing abdominal mass [ 20 - 22 ]. Although diagnostically challenging because it closely mimics much more common pathologies such as disc herniation or spinal stenosis, cord compression secondary to engorgement of the epidural venous plexus must be considered on the differential for all patients with an IVC filter who present with lower extremity pain or weakness [ 19 - 20 ]. With prompt diagnosis and intervention, complete resolution of these symptoms can be achieved.…”
Section: Discussionmentioning
confidence: 99%